Temperature Fluctuation Attenuates the Effects of Warming in Estuarine Microbial Plankton Communities - Cabrerizo, Marco J.; Marañón, Emilio; Fernández-González, Cristina; Alonso-Núñez, Adrián; Larsson, Henrik; Aranguren-Gassis, María (Frontiers in Marine Science, 2021)
Sea surface warming has the potential to alter the diversity, trophic organization and productivity of marine communities. However, it is unknown if temperature fluctuations that ecosystems naturally experience can alter the predicted impacts of warming. We address this uncertainty by exposing a natural marine plankton community to warming conditions (+3°C) under a constant vs. fluctuating (±3°C) temperature regime using an experimental mesocosm approach. We evaluated changes in stoichiometry, biomass, nutrient uptake, taxonomic composition, species richness and diversity, photosynthetic performance, and community metabolic balance. Overall, warming had a stronger impact than fluctuating temperature on all biological organization levels considered. As the ecological succession progressed toward post-bloom, the effects of warming on phytoplankton biomass, species richness, and net community productivity intensified, likely due to a stimulated microzooplankton grazing, and the community metabolic balance shifted toward a CO2 source. However, fluctuating temperatures reduced the negative effects of warming on photosynthetic performance and net community productivity by 40%. Our results demonstrate that temperature fluctuations may temper the negative effect of warming on marine net productivity. These findings highlight the need to consider short-term thermal fluctuations in experimental and modeling approaches because the use of constant warming conditions could lead to an overestimation of the real magnitude of climate change impacts on marine ecosystems.